Observations on the behaviour of pond pre-reared pikeperch under intensive rearing conditions - Molnár, Tamás; Hancz, Csaba; Molnár, Marcell (Acta Agraria Kaposváriensis, 2002)
Authors summarized the results of the ethological observations carried out on pike-perch fingerlings between 1999 and 2001. Some elements of intensive rearing techniques developed in catfish and trout culture can be applied for pike-perch with good efficiency, however important differences should be considered. The aim of our investigations was to determine the feeding habit of pike-perch fingerlings in the period of transition from zooplankton to lifeless feed, because this knowledge is essential for the elaboration of the intensive technique. It can be concluded that two rearing parameters (stocking density and different feed) have significant influence on the feeding behaviour that, on the other hand, is an important factor in survival rate and occurrence of cannibalism.
Keywords: pike-perch; behaviour; intensive rearing; stocking density